Cognitive deficits in methamphetamine addiction: Independent contributions of dependence and intelligence. (1st April 2020) - Fitzpatrick, Rebecca E.; Rubenis, Adam J.; Lubman, Dan I.; Verdejo-Garcia, Antonio
Highlights: Methamphetamine dependence impacts inhibitory control and decision-making. Intelligence better explains episodic and working memory deficits. Methamphetamine duration (not amount or frequency) linked to cognitive deficits. Abstract: Background: Methamphetamine's effects on brain function have been associated with cognitive deficits, which have a negative impact on clinical outcomes. However, it remains unclear if cognitive deficits relate to methamphetamine dependence (potentially amenable to abstinence and retraining) or background characteristics, mental health and other drug use. We tested the association between methamphetamine dependence and cognitive performance, while factoring in the impact of background characteristics, depressive symptoms and tobacco, alcohol and cannabis use. Method: The sample comprised 108 treatment-seeking participants who met the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV TR) criteria for methamphetamine dependence and 50 socio-demographically matched controls. We administered a comprehensive neuropsychological test battery (delay discounting, decision making, disinhibition, episodic and working memory) and examined cognitive deficits in methamphetamine users after taking into account socio-demographic characteristics, tobacco, alcohol and cannabis use, and depressive symptoms. Results: Hierarchical multiple regression analyses showed that methamphetamine dependence was associated with poorer performance in decision-making and disinhibition over and above other predictors, while IQ better explained performance in episodic and working memory. Although duration of methamphetamine use was linked to disinhibition, other patterns of methamphetamine use (including dose and frequency) were not consistently related to performance. Conclusions: Methamphetamine dependence impacts inhibitory control and decision-making, whereas lower IQ associates with memory/working memory deficits among methamphetamine users. Findings suggest the need to target disinhibition and impulsive decision-making as part of methamphetamine dependence treatment, while buffering the impact of IQ on memory systems.